Exchange-Rate Parities: Reply - Garnsey, Morris E. (Quarterly Journal of Economics, 1946)
Exchange-Rate Parities: Reply Get access Morris E. Garnsey Morris E. Garnsey University of Colorado Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 60, Issue 4, August 1946, Pages 624–630, https://doi.org/10.2307/1885155 Published: 01 August 1946